Pengembangan Media Pembelajaran Menulis Cerpen Berbasis E-Comic untuk Sma Kota Semarang - Khoiriyah, Sriani Uswatul; Djatun, Rahmat; Suwandi, Suwandi (TEKS, 2016)
This research aims to develop learning media by using media-based e-comic as a medium for writing short stories. Development of instructional media to write short stories based e-comic is achieved through four stages of development, namely (1) the preliminary stage, include; The theoretical and practical analysis, the analysis needs of teachers and learners, the drafting of model / prototype e-comic media, (2) the development stage, include; test experts validated by one person and one person matter expert media experts, the revision of the e-comic media, (3) the testing phase, covering; test the use of the product.